Double-booked: Effects of overlap between school and farming calendars on education and child labor - Allen IV, James (International Food Policy Research Institute, 2024)
Overlap between school and farming calendars—pervasive in agrarian settings—constrains children’s time for both activities, potentially forcing trade-offs between schooling and child labor. Using shift-share estimation, I study an exogenous shift to overlap between school and crop calendars in Malawi, weighted and aggregated by communities’ pre-policy crop shares, matched to panel data on school-aged children. From pre- to post-policy, a five-day (i.e., one school-week) increase in overlap during peak farming periods decreases children’s school advancement by 0.14 grades—one lost grade for every seven children—while only resulting in 3.9 percent fewer children working on the household-farm. Policy simulations show how adapting the school calendar to minimize overlap with peak farming periods can be an effective strategy to increase school participation.